(untitled) (Journal of Pharmaceutical Negative Results, 2022)
One of the most important scientific disciplines is determining the toxicity of heavy metals in freshwater, and there is a rising concern about the development of methodologies for identifying toxic effects in aquatic creatures. To test the efficacy of this approach, an experimental study was conducted on the fish Cyprinus carpio from a pond in Bengaluru, Karnataka. Surface bioaccumulation of mercury and lead on Cyprinus carpio was studies using Scanning Electron microscopy. Molecular bioaccumulation of Mercury and lead were analysed by ICPMS. Brain showed highest level of mercury (1780 ppb) when compared to kidney (1365 ppb) and liver (1150 ppb) tissues of C. carpio. Similarly, highest accumulation of lead noticed in brain (1490 ppb) followed by kidney (1245 ppb) and liver (1100 ppb). Moreover, mercury and lead surface accumulation and molecular bioaccumulation were highest in the brain compared to the liver and kidney Cyprinus carpio. The surface morphology of kidney, liver and brain is studied by scanning electron microscopy (SEM). This study has elicited a strong response from freshwater aquaculture to implement toxicity control measures and avoid future infiltration into the food chain. The present study has been undertaken to explore the toxic effects of lead and mercury on kidney, liver and brain of fish Cyprinus carpio and to detect the spectral biochemical and surface morphological changes.